Digital constitutionalism in Europe : reframing rights and powers in the algorithmic society - De Gregorio, Giovanni <<[VerfasserIn]>> (Cambridge studies in European law and policy, 2022)
"This is a book about rights and powers in the digital age. It is an attempt to reframe the role of constitutional democracies some in the information or network society, which, in the last twenty years, has transmuted into the algorithmic society as the current societal background where large, multinational social platforms 'sit between traditional nation states and ordinary individuals and the use of algorithms and artificial intelligence agents to govern populations'"--